Acute post-streptococcal glomerulonephritis: analysis of the pathogenesis. (8th September 2021) - Mosquera, Jesús; Pedreañez, Adriana
Abstract: Increasing evidence supports a central role of the immune system in acute post streptococcal glomerulonephritis (APSGN), but the current view of how streptococcal biology affects immunity, and vice versa, remains to be clarified. Renal glomerular immune complex deposition is critical in the initiation of APSGN; however, mechanisms previous to immune complex formation could modulate the initiation and the progression of the disease. Initial and late renal events involved in the nephritis can also be related to host factors and streptococcal factors. In this review we describe the mechanisms reported for the APSGN pathogenesis, the interactions of streptococcal products with renal cells and leukocytes, the possible effects of different nephritogenic antigens in the renal environment and the possibility that APSGN is not just due to a single streptococcal antigen and its antibody; instead, kidney damage may be the result of different factors acting at the same time related to both streptococcus and host factors. Addressing these points should help us to better understand APSGN physiopathology.